Burning the Rechtsstaat: legal institutions and protection of the rule of law. Issue 1 (29th June 2020) - Hartwell, Christopher A.; Urban, Mateusz
Abstract: The economic literature is clear that transparent and impartial rule of law is crucial for successful economic outcomes. However, how does one guarantee rule of law? This paper uses the idea of 'self-reinforcing' institutions to show how political institutions may derail rule of law if associated judicial institutions are not self-reinforcing. We illustrate this using the contrasting examples of Estonia and Poland to frame the importance of institutional context in determining both rule of law and the path of legal institutions. Although starting tabula rasa for a legal system is difficult, it worked well for rule of law in Estonia in the post-communist transition. Alternately, Poland pursued a much more gradualist strategy of reform of formal legal institutions; this approach meant that justice institutions, slow to shed their legacy and connection with the past, were relatively weak and susceptible to attack from more powerful (political) ones. We conclude that legal institutions can protect the rule of law but only if they are in line with political institutions, using their self-reinforcing nature as a shield from political whims of the day.